A Study to Identify Factors Responsible For Low Immunization Coverage in a High Priority District of Madhya Pradesh - Mahore, Ramniwas; Agarwal, Anil Kumar; Jamra, Vishal; Mahore, Rakesh Kumar (National Journal of Community Medicine, 2018)
Background: Yet the coverage against VPDs remains close to complete but there is a large gap between target and achievement of child immunisation in the country. The study was conducted to assess the dropout rate and primary immunization coverage of children aged 12-23 months in Raisen district of Madhya Pradesh and to know the various reasons for partially or not immunizing the child. Methods: A Community based cross sectional study carried out in the urban and rural area by WHO-Cluster sampling method. Sam- ple size was 900 children (30 children from each cluster) of aged 12-23 months. Results: The mean age of the study subjects was 17.27 months ± 3.32 SD. Overall 65.78% children were fully immunized, 29.11% were partially immunized and 5.11% of them were not immu- nized. A progressive increase was seen in the drop-out rate from the first to the third dose of DPT & Pentavalent vaccine. . The drop- out rate for primary immunization i.e. from BCG to Measles was found to be 7.5%. Obstacle and Lack of information were sig- nificant reasons for partial immunization of the children and lack of motivation was the major reason for not immunization. Conclusion: There is scope for improvement by focusing on the factors which are influencing utilization of immunization services.